Striking similarities between the regulatory mechanisms governing yeast mating-type genes and mammalian major histocompatibility complex genes. - Weissman, J D (1991)
Expression of a mammalian major histocompatibility complex (MHC) class I gene is in part regulated by a silencer DNA sequence element which binds a complex of silencer factors. This negative regulatory system is shown to be strikingly similar to the yeast alpha 2 mating-type repression system. A moderate DNA sequence homology exists between the MHC class I silencer DNA element and the yeast alpha 2 operator. Mammalian silencer factors specifically bind to the yeast alpha 2 operator DNA and also specifically interact with a yeast alpha 2-binding protein. Furthermore, the alpha 2 operator functions as a silencer element in mammalian cells when placed upstream of a MHC class I promoter.